Future Of Mathematical Modelling: A Review Of Covid-19 Infected Cases Using S-I-R Model - Azrul Azim Mohd Yunus; Arif Asraf Mohd Yunus; Muhammad Safwan Ibrahim; Shahrina Ismail (University of Baghdad, 2024)
Indexed by WOS